[Dr]illing in the name of: the criminalisation of Sydney drill group ONEFOUR. Issue 4 (2nd October 2022) - Lee, Murray; Martin, Toby; Ravulo, Jioji; Simandjuntak, Ricky
ABSTRACT: The criminalisation of hip-hop artists is not new. The focus of attention for police has tended to be on artists of colour (in particular) who include descriptions of violence in their lyrics. The sprawling multicultural western suburbs of Sydney Australia have become a fertile breeding-ground for a wave of drill rap artists, some of whom explore violent themes. This dynamic scene was kicked off by Pacifica group ONEFOUR. Popular internationally, ONEFOUR have been subject to prolonged police and media attention resulting in cancelled tours and untested allegations of criminality. This article uses a framework of musicriminology to explore the aesthetic and cultural elements of ONEFOUR's influence and infamy. It also places Australian drill music in its socio-historical and post-colonial context to explain why it has attracted censure. We suggest that ONEFOUR's brand of Australian drill represents a Western Sydney 'other'; a population both under-represented (in terms a cultural voice) and over-represented (in the criminal justice system) (Ahmad, 2013). The dark aesthetic, unnerving sonics and bleak lyrics of some drill exposes the underbelly of post-colonial neo-liberalism and groups economically excluded and socially marginalised. It tells stories abhorrent to moral gate-keepers and creating an atmosphere of geo-spatialised and sonically-informed danger.